1999
DOI: 10.1063/1.125165
|View full text |Cite
|
Sign up to set email alerts
|

Scanning nonlinear dielectric microscopy with nanometer resolution

Abstract: A very high-resolution scanning nonlinear dielectric microscope was developed for the observation of ferroelectric polarization. We demonstrate that the resolution of the microscope is of a nanometer order by measurement of the c–c domain wall of a BaTiO3 single crystal, and that this microscope is very useful not only for the domain observation of ferroelectric bulk material but also for that of thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
98
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(98 citation statements)
references
References 5 publications
0
98
0
Order By: Relevance
“…Further improvements incorporated a resonant structure at the probe end of the transmission line [9]. Monitoring the change of resonant frequency and quality factor (Q), several groups have demonstrated different designs of resonant NSMMs with very high sensitivity and spatial resolution [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Further improvements incorporated a resonant structure at the probe end of the transmission line [9]. Monitoring the change of resonant frequency and quality factor (Q), several groups have demonstrated different designs of resonant NSMMs with very high sensitivity and spatial resolution [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In PEEM, excitation by polarized x-ray synchrotron radiation tuned to atomic absorption edges leads to the emission of secondary electrons at the sample surface, which are used to make an image of the sample. [30][31][32][33] It has been demonstrated that PEEM is capable of probing domain dynamics at nanosecond time resolution and sub-micron spatial resolution. 32,33 However, in general PEEM is unable to probe length scales less than 20-50 nm (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution of the technique is comparable or better to that of PFM though the temporal resolution suffers because of the need to scan a probe as in PFM. 31 At the same time, there have been remarkable advances in electron microscopy that have direct implications for the study of these materials, especially in the field of in situ TEM. [24][25][26][27]34 In situ TEM is a strong candidate to investigate domain switching phenomena over a critical spatial and temporal range.…”
Section: Introductionmentioning
confidence: 99%
“…From the DE hysteresis measurement of PZT thin film deposited by the hydrothermal method on SrRuO 3 /SrTiO 3 substrate, an imprint was too large to reverse and maintain the intended poling direction as shown later. Hence; this PZT thin film was not suitable for a FeRAM application and ultra-high density storage medium to construct a nano dot pattern with a conductive atomic force microscopy (AFM) probe [2][3][4][5]. The composition ratio of Zr/Ti in the deposited PZT film was controlled in an effort to achieve the morphotropic phase boundary (MPB).…”
Section: Introductionmentioning
confidence: 99%
“…A domain wall thickness of the ferroelectric material is very thin compared to that of the ferromagnetic materials [1], so that a ferroelectric ultra-high density data storage system attracts researcher's attentions [2][3][4][5] To write and pick up the data bit a scanning nonlinear dielectric microscopy system is superior to piezoelectric force microscopy due to its superior resolution [2][3][4][5]. Up to now, 1.5Tbit/inch 2 data storage density has been demonstrated using congruent lithium tantalate thin films [2].…”
Section: Introductionmentioning
confidence: 99%